Pemikiran Epistemologi Barat: dari Plato Sampai Gonseth - Nunu Burhanuddin (Pusat Penelitian dan Penerbitan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Raden Fatah Palembang, 2015)
This paper riviewing the Western epistemology thought. The theme focuses on Plato to Gonseth. The Epistemology that referred in this article, is to think about